A Girardian Reading of the Qu”™ranic Denial of the Crucifixion - Andrade, Gabriel (Opción)
The Qu”™ran states that, contrary to Christian doctrine, Jesus of Nazareth did not die on the cross, but was raised to heaven by God. Some XVIII Cent. European theologians have also suggested that Jesus may have survived the crucifixion. Christians have been in need of refuting the Qu”™ran”™s denial of the crucifixion, but they lack the required archaeological and historical data to do so. However, the work of French thinker René Girard may be a useful tool to affirm the veracity of Jesus”™ crucifixion. Girard”™s anthropology suggests that stories that deny murders are in fact a way of covering our cultural origins.